Transcriptional analysis identifies potential biomarkers and molecular regulators in pneumonia and COPD exacerbation - Bertrams, Wilhelm; Griss, Kathrin; Han, Maria; Seidel, Kerstin; Klemmer, Andreas; Sittka-Stark, Alexandra; Hippenstiel, Stefan; Suttorp, Norbert; Finkernagel, Florian; Wilhelm, Jochen; Greulich, Timm; Vogelmeier, Claus F.; et al. (Scientific Reports, 2020)
Lower respiratory infections, such as community-acquired pneumonia (CAP), and chronic obstructive pulmonary disease (COPD) rank among the most frequent causes of death worldwide. Improved diagnostics and profound pathophysiological insights are urgent clinical needs. In our cohort, we analysed transcriptional networks of peripheral blood mononuclear cells (PBMCs) to identify central regulators and potential biomarkers. We investigated the mRNA- and miRNA-transcriptome of PBMCs of healthy subjects and patients suffering from CAP or AECOPD by microarray and Taqman Low Density Array. Genes that correlated with PBMC composition were eliminated, and remaining differentially expressed genes were grouped into modules. One selected module (120 genes) was particularly suitable to discriminate AECOPD and CAP and most notably contained a subset of five biologically relevant mRNAs that differentiated between CAP and AECOPD with an AUC of 86.1%. Likewise, we identified several microRNAs, e.g. miR-545-3p and miR-519c-3p, which separated AECOPD and CAP. We furthermore retrieved an integrated network of differentially regulated mRNAs and microRNAs and identified HNF4A, MCC and MUC1 as central network regulators or most important discriminatory markers. In summary, transcriptional analysis retrieved potential biomarkers and central molecular features of CAP and AECOPD.
CRIS-Team Scopus Importer:2020-02-07